Antibodies to adalimumab are associated with future inflammation in Crohn's patients receiving maintenance adalimumab therapy: a post hoc analysis of the Karmiris trial. Issue 7 (10th April 2015) - Baert, Filip; Kondragunta, Venkateswarlu; Lockton, Steven; Vande Casteele, Niels; Hauenstein, Scott; Singh, Sharat; Karmiris, Konstantinos; Ferrante, Marc; Gils, Ann; Vermeire, Séverine
Abstract : Introduction: Data on immunogenicity to adalimumab (ADL) therapy in patients with IBD is limited. We performed additional analyses on the Karmiris cohort using the homogeneous mobility shift assay (HMSA) focusing on the inter-relationship of serum ADL concentration, antibodies-to-adalimumab (ATA), inflammatory markers and sustained response. Methods: 536 prospectively collected serum samples were available for analysis of ADL concentration and ATA using HMSA. We studied the role of week 4 serum ADL concentration and immunomodulator (IMM) use on ATA formation with a Cox proportional hazards model. Mixed model repeated measures analysis was performed to assess the independent effects of serum ADL concentration and ATA on C-reactive protein (CRP) and response. Results: ATA was detected in 20% of patients after a median of 34 (12.4–60.5) weeks. ATA-positive samples correlated with lower serum ADL concentration (p<0.001). Cox regression modelling showed that week 4 ADL concentration of <5 µg/mL significantly increased the future risk of ATA formation (HR=25.1; 95% CI 5.6 to 111.9; p=0.0002) and that IMM co-treatment prevented ATA formation (HR=0.23; 95% CI 0.06 to 0.86; p=0.0293). Regression modelling showed a negative correlation between CRP and ADL concentration (p=0.0001) and a positive one with ATA (p=0.0186). The model revealed that both lower serum ADL concentration and ATA were independently associated with future CRP (p=0.0213 and p=0.0013 respectively). ATA positivity was associated with discontinuation of ADL because of loss or response (OR=3.04; 95% CI 1.039 to 9.093; p=0.034). Conclusions: ATA were detected in 20% of patients. Risk of ATA formation increased with lower early serum ADL concentration and in patients not on IMM. ATA and ADL were strongly associated with higher future CRP level and discontinuation of ADL.